Short-term exposure to air pollutants increases the risk of ST elevation myocardial infarction and of infarct-related ventricular arrhythmias and mortality. (1st January 2018) - Bañeras, Jordi; Ferreira-González, Ignacio; Marsal, Josep Ramon; Barrabés, José A.; Ribera, Aida; Lidón, Rosa Maria; Domingo, Enric; Martí, Gerard; García-Dorado, David; ,
Abstract: Background: The relation between STEMI and air pollution (AP) is scant. We aimed to investigate the short term association between AP and the incidence of STEMI, and STEMI-related ventricular arrhythmias (VA) and mortality. Methods: The study was carried out in the area of Barcelona from January 2010 to December 2011. Daily STEMI rates and incidence of STEMI-related VA and mortality were obtained prospectively. The corresponding daily levels of the main pollutants were recorded as well as the atmospheric variables. Three cohorts were defined in order to minimize exposure bias. The magnitude of association was estimated using a time-series design and was adjusted according to atmospheric variables. Results: The daily rate of hospital admissions for STEMI was associated with increases in PM 2.5, PM 10, lead and NO2 concentrations. VA incidence and mortality were associated with increases in PM 2.5 and PM 10 concentrations. In the most specific cohort, BCN (Barcelona) Attended & Resident, STEMI incidence was associated with increases in PM 2.5 (1.009% per 10 μg/m 3 ) and PM 10 concentrations (1.005% per 10 μg/m 3 ). VA was associated with increases in PM 2.5 (1.021%) and PM 10 (1.015%) and mortality was associated with increases in PM 2.5 (1.083%) and PM 10 (1.045%). Conclusions: Short-term exposure to high levels of PM 2.5 and PM 10 is associated with increased daily STEMI admissions and STEMI-related VA and mortality. Exposure to high levels of lead and NO2 is associated with increased daily STEMI admissions, and NO2 with higher mortality in STEMI patients.